A Nonstandard Neutrosophic α-Discounting Evaluation Model for Teaching Ability Assessment of Vocational Colleges Teachers - Song Gu (Neutrosophic Sets and Systems)
Evaluating the teaching ability of vocational college teachers is complex due to uncertain, vague, and conflicting expert opinions. This research presents a new method that combines the Interval α-Discounting approach with the Nonstandard Neutrosophic Complex MoBiNad framework. The model allows expert judgments to include uncertainty and partial truth, then adjusts them using mathematical discounting to reach a stable solution. A real case study involving several teachers and criteria is used to test the method. The process includes detailed equations, full calculations, and real-world data. Results show that the method gives fair and reliable scores, even when opinions are not fully clear or consistent. This hybrid model can help improve decision-making in educational evaluation systems.